Assessment of Antibiotic Prescribing Patterns at Outpatient Pharmacy Using World Health Organization Prescribing Indicators - Dawit Kumilachew Yimenu; Abdurazak Emam; Endilik Elemineh; Wagaye Atalay (SAGE Publishing, 2019)
Background: Overuse of antibiotics is a common problem in health care, which leads to unnecessary expenditure on drugs, raised risk of adverse reactions, and the development of antimicrobial resistance. Inappropriate prescribing habits lead to ineffective and unsafe treatment, worsening of disease and increment of health care costs. The aim of this study was to assess antibiotic prescribing patterns using World Health Organization prescribing indicators at the outpatient Pharmacy Department of University of Gondar referral hospital, Gondar, Northwest Ethiopia. Methods: A retrospective cross-sectional study was conducted. One-year prescription data was collected from prescription and prescription registration books retained at the pharmacy store. World Health Organization/International Network of Rational Use of Drugs prescribing indicators were utilized to measure rational use of drugs with due focus on antibiotics prescribing patterns. The collected data was analyzed using SPSS version 20. Results and Discussion: A total of 968 drugs were prescribed from 600 patient encounters. The average number of drugs per encounter was 1.6. The percentage of encounters in which an antibiotics and injections were prescribed was 69.7% and 6.3% respectively. Amoxicillin (28.5%) followed by ciprofloxacin (12%) and metronidazole(11.1%) were the most commonly prescribed antibiotics. The percentage of drugs prescribed from essential drugs list and by generic name was 95.3% and 96%, respectively. Rate of antibiotics prescribing showed deviation from the standard recommended by World Health Organization whereas polypharmacy, injectable prescribing pattern, uses of brand names, and prescription of drugs from the National Essential Drugs List were not found to be a significant problem though there were slight deviations from the standard. Conclussion: Interventions aimed at improving the antibiotic prescribing patterns need to be implemented so as to prevent the inappropriate use of antibiotics and avoid further complications.